Cardiorespiratory, haematological and rectal temperature changes of Friesian and friesian X L.I.D cows to Malaysian climate - Kassim, H.; Azahar, I. (Malaysian Society of Applied Biology, 1984)
The effect of hot humid Malaysian climate on the cardiorespiratory activities, haematological values and rectal temperature were observed in the Friesian and Friesian x LID cows. Respiratory rate, rectal temperature and pulse rate of both breeds increased as the ambient temperature increased. The increments were more pronounced when the animals were exposed to direct sunlight, and these animals too showed a greater reduction in erythrocyte count, haemoglobin level and packed cell volume compared to those cows kept under the shed. Blood pH of both breeds increased slightly indicating hyperventilation of the respiratory system. The result had shown an increase in heat tolerance of the crossbreds compared to the pure Friesian cows.